Material editorial como apoyo para el tratamiento de niños con trastorno de déficit de inatención e hiperactividad (TDAH) en ABA CENTER Ambato - Tamayo Cushpa, Christian Andrés (2024)
ADHD is a physical, psychological and social problem that affects a large part of the child population, for this reason this project covers this problem from the strategic and planning area, which involves the section of addressing and coping with this problem, as a practical tool through the editorial design involved in the creation of a book of activities with a focus on cognitive and behavioral therapy, based on a mixed approach with deductive methodology in which involves the modality of bibliographic research mainly used for information gathering. In addition, it implies the use of interviews as a tool for the socialization of qualitative criteria in the professional field of the different branches selected for the fulfillment of the objectives, in order to build a remarkable and functional product, involving three important aspects such as "Psych pedagogical Institutions", "The publishing house" and a focus group to parents directed to solve and collect important aspects for the development of this material. As a result, an editorial proposals was obtained, which consists of a book of cognitive-behavioral activities, with a very entertaining and eyes-catching design that allows the capture of attention and the development of the child in an entertaining and didactic ways, oriented to the formations of parents by means of a tools for the resolutions of behaviors in a didactic and attentionally way through the guidance, direction and training of parents as well as personnel of the institution "ABA CENTER"